Nurses' experiences regarding nursing competence in the isolation wards during COVID-19 pandemic - Arista Maisyaroh; Eko Prasetya Widianto; Syaifuddin Kurnianto; Rizeki Dwi Fibriansari (PAGEPress Publications, 2024)
During the COVID-19 pandemic, it was essential for nurses to possess the necessary skills and expertise to provide care for patients in isolation wards designated for COVID-19 cases. This recognition of a nurse's experience could serve as a basis for establishing more precise competency standards for staff working in COVID-19 isolation wards. This study aimed to explore the experience of nurses with the competencies needed to care for COVID-19 patients in the isolation ward. The research design used was a phenomenological design as outlined by van Manen's phenomenological of practice. In-depth interviews were conducted using semi-structured questions involving six nurses in the COVID-19 isolation ward at Lumajang District Hospital. This study found seven major themes, namely nurses must have altruistic thinking, critical thinking to solve problems, the ability to work with teams, problem-solving thinking, the ability to handle emergency situations, have a caring attitude, and have the motivation to learn. The competence of nurses in the COVID-19 isolation ward should be established on a foundation of both hard and soft skills, which are essential for a nurse to deliver optimal care to COVID-19 patients. Efforts aimed at enhancing nurses' competencies should take precedence, enabling them to provide improved care and assist in addressing the ongoing public health challenges.